Willingness to Pay and Compensation Demanded: Experimental Evidence of an Unexpected Disparity in Measures of Value - Knetsch, Jack L.; Sinden, J. A. (Quarterly Journal of Economics, 1984)
Aside from possible income effects, measures of the maximum amounts people will pay to avoid a loss and the minimum compensation necessary for them to accept it are generally assumed to be equivalent. Unexpectedly wide variations between these sums, however, have been noted in survey responses to hypothetical options. This paper reports the results of a series of experiments that confronted people with actual money payments and cash compensations. The results indicate that the compensation measure of value seems to exceed significantly the willingness to pay measure, which would appear to call into some question various rules of entitlement, damage assessments, and interpretations of indifference curves.